Phenotyping and association analysis of grain zinc content with agro-morphological traits in a core rice germplasm - Tripathy, Swapan K.; Behera, Suraj K.; Sahu, Dibyabharati (AkiNik Publications, 2020)
A set of 47 biofortified core germplasm lines of rice were estimated for grain zinc (Zn) content to explore high Zn donors and to determine the degree of association of Zn content with agro-morphological traits including seed yield. The top Zn dense (≥20ppm) genotypes identified were Nagina 22 (28.1ppm), BG 102(25.8ppm), Dudh Kandar (25.6ppm), R-RHZ-7 (24.7ppm) and IR 85850-AC157-1 (24.0ppm). R-RHZ-7 recorded maximum EBT/m2 along with long panicle, while Nagina 22 maintained dwarf plant type with excellent grain fertility (≥92%), thin hull and known high degree of drought tolerance. Among these, IR 85850-AC157-1(24.0ppm) and R-RHZ-7 (24.7ppm) retained high grain zinc content along with moderately high seed yield potential. Grain number/panicle (r=0.757**), days to flowering, days to maturity and fertility percentage revealed strong positive correlation with seed yield. Grain Zn content had non-significant negative association with seed yield indicating genetic enhancement for Zn may not have much yield penalty. Interestingly, Zn content revealed positive significant relationship with grain breadth, but feeble negative association with grain length and kernel length indicating that selection for bold grain types would enrich Zn content. The above Zn rich elite genotypes with desirable ancillary traits may serve as potential donors for biofortification breeding programme.